Descriptive analysis of corneal maps and anterior segment tomography of the rabbit eye using dual Scheimpflug and Placido Disc tomography - Leticia de Andrade Ramos; Carlos Guillermo Arce; Cláudia Valéria Seullner Brandão; Lenise Garbelotti Gonçalves; Carlos Roberto Padovani (Ciência Rural, 2025)
ABSTRACT: This study described corneal maps and anterior-segment tomography images of rabbits’ eyes. The exams of 10 male 14-month-old rabbits (20 eyes) were analyzed. The animals were sedated and evaluated using a Galilei G4. The following maps were analyzed qualitatively: axial and instantaneous curvature, pachymetry, total corneal power, best-fit sphere (BFS) and best-fit toric asphere (BFTA) elevation, in addition to anterior-segment tomography images. The curvature maps were aspheric. A doughnut-shaped ring was observed in the posterior instantaneous curvature map. No patterns were observed in the elevation maps. The total corneal power (TCP) maps were multifocal and the TCP increased from the center to the periphery of the cornea. The pachymetry maps were uniform, without the pachymetry progression pattern seen in the human cornea. To the best of our knowledge, this is the first research to analyze in detail the topographic maps of rabbits’ corneas using the Galilei device. The maps were aspheric prolate, multifocal and uniformly thin; the anterior chamber was shallow; and the lens was spherical. In view of the importance of this species as an experimental model, the relevance of studies concerning rabbit corneal characteristics is highlighted.